Incidence rate of symptomatic painless thyroiditis presenting with thyrotoxicosis in Denmark as evaluated by consecutive thyroid scintigraphies. (April 2013) - Schwartz, Frederik; Bergmann, Natasha; Zerahn, Bo; Faber, Jens
Abstract Background. Painless thyroiditis (PT) is a transient kind of thyrotoxicosis, with lack of uptake on a thyroid scintigraphy in a non-tender thyroid gland, elevated anti-TPO antibodies, no fever, no history of increased iodine intake, and a normal sedimentation rate. The prevalence of PT varies hugely in the literature. Objective. To establish the incidence rate of PT in Denmark as well as to describe the phenotype of PT in more detail. Methods. Tc-99m pertechnetate scintigraphies were performed over a period of 9.75 years on 6022 consecutive patients (2349 had a thyrotoxic episode), and were divided into high or normal (5528), reduced (300) or lack of uptake (194). Patient records were evaluated: 292 with reduced, and 186 with lack of uptake. As a control measure, 230 consecutive thyrotoxic patients were also analyzed. Results. Based on scintigraphies, 12 patients had PT, 10 with lack of uptake and two with reduced, corresponding to an incidence rate of 0.49/100, 000 person years. It was predicted, that only one patient among the newly diagnosed consecutive thyrotoxic cohort had PT. This patient was identified. The prevalence of PT among thyrotoxic patients was 0.51% as evaluated by scintigraphy, and 0.43% among the biochemically thyrotoxic patient cohort. Twenty-five percent had more than one thyrotoxic episode, 75% had at least one subsequent hypothyroid episode, and 33% developed permanent hypothyroidism. Conclusions. PT presenting with symptomatic thyrotoxicosis is an extremely rare disease in Denmark. Symptomatic PT presents most often with no uptake on a Tc-99m pertechnetate scintigraphy. Clinical follow-up is essential.